Exploring the History, Uses, and Dangers of Belladonna: Unveiling the Mysteries of the Deadly Nightshade - Nikandish, Mehrasa; Nikandish, Mohamad (European Scientific Journal, ESJ, 2024)
Belladonna (Atropa belladonna) is a plant with a rich history, renowned for its beauty and lethality. This review synthesizes existing literature to provide an overview of belladonna, covering its historical significance, medicinal uses, toxicity, regulatory status, and cultural references. Belladonna’s alkaloids, such as atropine and scopolamine, have medicinal value but pose significant risks due to their high toxicity. Recent research explores their pharmacotherapeutic potential, yet controversies persist regarding their safety and regulation. Safety precautions are paramount due to the plant’s extreme toxicity. This review underscores the need for informed decision-making and further research to navigate the complexities of belladonna’s use in contemporary healthcare.